Understanding the Impact of Web 2.0 and Social Media on English Language Learning and Teaching: A Systematic Literature Review - Md. Minhaz Uddin; Saifullah Saif; Sidratul Montaha (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2022)
This study implies to analyses the significance of Web 2.0 and Social Media in terms of English language learning and teaching. A structural literature based analyses has been conducted to interpret the objectives. Social media has significant contribution in English language learning as well as teaching. Advanced technology make sure that, social media tools are available all over the world. Learning English is an indicator of quality improvement through the least development countries and developing countries whatever, developed countries also viable to increase the proficiency of English language. Practicing English in social media is popular in young generation via inside or outside of classroom. This investigation contribute to sum up a review of contribution as well as consequences of social media in teaching learning strategy, which is able to increase the value in existing research.